Sustainable Community Development Step 6: Carry Out Projects and Monitor, Evaluate and Make Adjustments as Needed - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS)
This document explains how to evaluate your project and use sustainability indicators to measure progress. The document includes the 10 steps of the Bellagio Principles used to measure and assess progress towards sustainability. This document is FCS7219-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.